Neurological and Vascular Manifestations of Ethylmalonic Encephalopathy - TAVASOLI, Alireza; ROSTAMI, Parastoo; ASHRAFI, Mahmoud reza; KARIMZADEH, Parvaneh (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Tavasoli AR, Rostami P, Ashrafi MR, Karimzadeh P. Neurological and Vascular Manifestations of Ethylmalonic Encephalopathy. Iran J Child Neurol. Spring 2017; 11(2):57-60. Abstract Objective Ethylmalonic encephalopathy (EE) is a severe mitochondrial disease of early infancy clinically characterized by a combination of developmental delay, progressive pyramidal signs, and vascular lesions including petechial purpura, orthostatic acrocyanosis, and chronic hemorrhagic diarrhea. Biochemical hallmarks of the disease are persistently high level of lactate, and C4–C5-acylcarnitines in blood, markedly elevated urinary excretion of methylsuccinic and ethylmalonic (EMA) acids. Here we report two patients with EE as a 16-months-old male infant and a 2-yr-old boy referred to Pediatric Neurology Clinic in Children’s Medical Center, Tehran-Iran that in one patient genetic analysis revealed a homozygous mutation of the ETHE1 gene in favor of ethylmalonic acidemia. References 1. Tiranti V, D’Adamo P, Briem E, Ferrari G, Mineri R, Lamantea E. Ethylmalonic encephalopathy is caused by mutation in ETHE1, a gene encoding a mitochondrial matrix protein. Am J Hum Genet 2004; 74:239-252. 2. Di Meo I, Fagiolari G, Prelle A, Viscomi C, Zeviani M, Tiranti V. Chronic exposure to sulfide causes accelerated degradation of cytochrome c oxidase in ethylmalonic encephalopathy. Antioxid Redox Signal 2011; 15:353– 362. 3.Zafeiriou DI, Augoustides-Savvopoulou P, Haas D, Smet J, Triantafyllou, Vargiami E. Ethylmalonic encephalopathy: clinical and biochemical observations. Neuropediatrics 2007; 38:59-60. 4. UluçYis, IpekPolat, PakizeKarakaya, MügeAyanoglu, AyseSemraHiz. Importance of acrocyanosis in delayed walking. J Pediatr Neurosci 2015; 10(1):80-81. 5.Garcia-Silva MT, Ribes A, Campos Y, Garavaglia B, Arenas J Grosso S, Mostardini R, Farnetani MA, Molinelli. Syndrome of encephalopathy, petechiae, and ethylmalonic aciduria. Pediatr Neurol 1997; 17:165–170. 6. Tiranti V, Briem E, Lamantea E, Mineri R, Papaleo E, De Gioia L, et al. ETHE1 mutations are specific to ethylmalonic encephalopathy. J Med Genet 2006; 43:340-346. 7. Heberle Lada Cindro LC, Al Tawari Asma A AA, Ramadan Dina G DG, Ibrahim Jamila K JK. Ethylmalonic encephalopathy report of two cases. Brain & Development 2006; 28(5):329–331. 8. Mineri R, Rimoldi M, Burlina AB. Identification of new mutations in the ETHE1 gene in a cohort of 14 patients presenting with ethylmalonic encephalopathy. J Med Genet 2008; 45:473-478. 9. H.R. Yoon, S.H. Hahn, Y.M. Ahn, S.H. Jang, Y.J. Shin, E.H. Lee, K.H. Ryu, B.L. Eun, P.Rinaldo, S. Yamaguchi. Therapeutical trial in the first three Asian cases of ethylmalonic encephalopathy: response to riboflavin. J Inherit Metab Dis 2001; 24:870–873. 10. Maja Di Rocco, Ubaldo Caruso, Egill Briem, Andrea Rossi, Anna E.M. Allegri, Davide Buzzi, Valeria Tiranti. A case of ethylmalonic encephalopathy with atypical clinical and biochemical presentation. Mol Gen Metab 2006; 89:395–397. 11. Mohammed Owaidha Al-Ajmi, Satheesh Kalanthra Kutty. Ethylmalonic Aciduria Encephalopathy with Respiratory Failure and Nephrotic Syndrome Rare Presentation. Middle East J Fam Med 2005; 3(3). 12. Laura Papetti, Giacomo Garone, Livia Schettini, Carla Giordano, Francesco Nicita, Paola Papoff, Massimo Zeviani, Vincenzo Leuzzi, Alberto Spalice. Severe early onset ethylmalonic encephalopathy with West syndrome. Metab Brain Dis 2015; Jul 21. 13. Dweikat I, Naser E, Damsah N, Libdeh BA, Bakri I. Ethylmalonic encephalopathy associated with crescentic glomerulonephritis. Metab Brain Dis 2012; 27(4):613-6. 14. Nowaczyk MJ, Blaser SI, Clarke JT. Central nervous system malformations in ethylmalonic encephalopathy. Am J Med Genet 1998; 75:292–6. 15. Christodoulou J, Petrova-Benedict R, Robinson BH, Jay V, Clarke JTR. An unusual patient with the neonatal Marfan phenotype and mitochondrial complex I deficiency. Eur J Pediatr 1993; 152:428–432. 16. Chen E, Jurecki ER, Rinaldo P, Keilman C, Packman S, Johnston K. Nephrotic syndrome and dysmorphic facial features in a new family of three affected siblings with ethylmalonic encephalopathy. Am J Hum Genet 1994; 55:A2000. 17. Lehnert W, Ruitenbeek W. Ethylmalonic aciduria associated with progressive neurological disease and partial cytochrome c oxidase deficiency. J Inherit Metab Dis 1993; 16:557–559. 18. Garavaglia B, Colamaria V, Carrara F, Tonin P, RimoldiM,Uziel G. Muscle cytochrome c oxidase deficiency in two Italian patients with ethylmalonic aciduria and peculiar clinical phenotype. J Inherit Metab Dis 1994; 17:301–303. 19. Ozand PT, Rashed M, Millington DS, SakatiN,Hazzaa S, Rahbeeni Z, al OdaibA,Youssef N, Mazrou A,Gascon GG. Ethylmalonic aciduria: an organic acidemia with CNS involvement and vasculopathy. Brain Dev 1994; 16: 12–22. 20. Burlina AB, Dionisi-Vici C, Bennett MJ, Gibson KM, Servidei S, Bertini E, Hale DE, Schmidt-Sommerfeld E, Sabetta G, Zachello F, Rinaldo P. A new syndrome with ethylmalonic aciduria and normal fatty acid oxidation in fibroblasts. J Pediatr 1994; 125:79–86.